PERAN WALI KELAS DALAM UPAYA MENINGKATKAN MINAT BELAJAR SISWA DI SD JARINABI - Azlina, Nur; Nurfadlilah Muhyi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In this study, the author intends to describe the role of the homeroom teacher in efforts to increase student learning interest at Jarinabi Elementary School. The author uses a qualitative approach and descriptive methods. Where, the data obtained are based on the results of observations, interviews, and documentation with informants principal, homeroom teacher, and students. Then the data obtained will be analyzed through data reduction, data presentation, and drawing conclusions. Based on the data obtained, the results of this study indicate that a homeroom teacher has an important part in efforts to increase student learning interest through three main roles, namely as a class manager, motivator, and mentor. As a class manager, the homeroom teacher creates a conducive learning environment through classroom arrangement, as a motivator, the homeroom teacher fosters a spirit of learning through a variety of fun learning methods, providing verbal motivation, and appreciation to students. Also, as a mentor, the homeroom teacher can build personal relationships with students, help resolve academic and social-emotional problems, and have a good relationship with parents in terms of communication. Based on the results of the research that has been conducted, researchers can draw a conclusion that homeroom teachers have an important part and role, both in creating a comfortable, effective and enjoyable learning atmosphere so that they can help to increase students' interest in learning. Keywords: Homeroom teacher, learning interest, classroom management, learning motivation, student guidance